Current Issues in Knowledge Management - Wickham, Mark (IntechOpen, 2019)
The knowledge management concept has emerged to serve as one of the critical inputs to the strategic management process, and a common factor underpinning competitive advantage. Over the concept's development, knowledge management research has focused on the processes that enable a firm to recognize sources of data, to transform data into useful information, to disseminate the information, and to develop strategies based on its insights. More recently, the development of the concept has begun to focus on the critical antecedents that enable these knowledge management processes to be implemented more effectively and efficiently. This research book serves to highlight some of the antecedents of effective knowledge management through empirical research done by researchers all around the globe.